Dynamic Alterations in Salivary Microbiota Related to Dental Caries and Age in Preschool Children With Deciduous Dentition: A 2-Year Follow-Up Study - Xu, Lei; Chen, Xi; Wang, Yuan; Jiang, Wen; Wang, Sa; Ling, Zongxin; Chen, Hui (Frontiers in Physiology, 2018)
Dynamic alterations in oral microbiota are closely related to the development of dental caries;however, changes in salivary microbiota during this process have not been extensively studied. In addition, increasing evidence suggests that oral microbiome profiles differ according to dentition stages, but it is unclear whether they change with age during the same dentition , such as deciduous dentition. These two aspects were investigated in a 2-year follow-up study, and caries-free preschool children with complete deciduous dentition were enrolled. Saliva was collected and oral examination was conducted at the beginning of this trial, and then every subsequent 6 months for a total of five time points (T0, T1, T2, T3, and T4). Based on the clinical examination of teeth at the end of the trial, subjects were divided into health-to-health (H-H, N = 11) and health-to-caries (H-C, N = 12) groups at every time point. A total of 115 saliva samples from 23 subjects was detected by sequencing 16S rDNA V3-V4 hypervariable regions with the Illumina MiSeq platform to obtain microbiome profiles, and 100 samples finally passed quality control for further analyses. A total of 4,328,852 high-quality sequencing reads passed quality-control testing, representing 14 phyla, 27 classes, 43 orders, 67 families, and 127 genera. An α diversity analysis showed that salivary microbial diversity was similar in all groups, and a β diversity analysis showed that salivary microbial community structure changed with dental caries. Linear discriminant analysis effect size (LEfSe) analysis revealed that the abundance of the genera Atopobium, Megasphaera, and Veillonella increased significantly, while that of the genera Shuttleworthia and Rothia decreased significantly with the development of dental caries. Megasphaera and Veillonella were enriched at the early stage of deciduous dentition whereas Peptococcus, Rothia, and Treponema were enriched at the later stage. The core microbiome in the H-H and H-C groups comprised 26 and 29 genera, respectively, with statistical differences observed in 11 shared core genera. These results provide new insights into variations in the salivary microbiome related to dental caries and age in the deciduous dentition period.